The influence of culture and religion on visual privacy - Abdul Rahim, Zaiton (Elsevier Ltd., 2015)
This paper examines the influence of culture and religion on the conception of visual privacy, its regulation, and housing design attributes affecting visual privacy of Malay Muslim families living in terrace housing, in Malaysia. The study involves a survey interview of 381 respondents and 11 case studies. Findings indicate that changes in living condition in the urban area, a new paradigm in culture-housing and the lack of consideration for visual privacy in housing design, the conception of visual privacy and its regulation are influenced by both the Malay culture and Islam as a way of life.